103k views
2 votes
Rewrite this polynomial in terms of its simplest factors using the appropriate method: x3 + x2 − 6x.

User Broseph
by
6.0k points

2 Answers

5 votes

Answer:

x(x + 3)(x - 2)

Explanation:

Factor out x from each term

= x(x² + x - 6)

To factor the quadratic

Consider the factors of the constant term (- 6) which sum to give the coefficient of the x - term (+ 1)

The factors are + 3 and - 2, since

+ 3 × - 2 = - 6 and + 3 - 2 = + 1, hence

x² + x - 6 = (x + 3)(x - 2)

---------------------------------------

x³ + x² - 6x = x(x + 3)(x - 2) ← in factored form

User Cyral
by
5.6k points
5 votes

Answer: GCF = x

Explanation:

x(x^3/x + x^2/x + -6x/x)

x(x^2 + -6)

x(x - 2)(x + 3)

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.